Your Florida Dooryard Citrus Guide - Common Pests, Diseases, and Disorders of Dooryard Citrus - James J. Ferguson (EDIS, 2002)
This document is HS 890, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Originally published in hardcopy, 1995. Publication date: August, 2002.